2021
DOI: 10.1038/s41598-021-88895-0
|View full text |Cite
|
Sign up to set email alerts
|

Inducible knockout of Clec16a in mice results in sensory neurodegeneration

Abstract: CLEC16A has been shown to play a role in autophagy/mitophagy processes. Additionally, genetic variants in CLEC16A have been implicated in multiple autoimmune diseases. We generated an inducible whole-body knockout, Clec16aΔUBC mice, to investigate the loss of function of CLEC16A. The mice exhibited a neuronal phenotype including tremors and impaired gait that rapidly progressed to dystonic postures. Nerve conduction studies and pathological analysis revealed loss of sensory axons that are associated with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 70 publications
3
8
0
Order By: Relevance
“…A global knockout of CLEC16A in mice leads to abnormal mitophagy, upregulated inflammatory cytokine response, and increased risk of autoimmunity [12]. Interestingly, the knockout mice also develop severe neurological phenotypes with impaired gait and dystonic postures [13]. This is consistent with previous observations in two other mouse strains carrying independent constitutive CLEC16A mutations [14].…”
Section: Introductionsupporting
confidence: 89%
“…A global knockout of CLEC16A in mice leads to abnormal mitophagy, upregulated inflammatory cytokine response, and increased risk of autoimmunity [12]. Interestingly, the knockout mice also develop severe neurological phenotypes with impaired gait and dystonic postures [13]. This is consistent with previous observations in two other mouse strains carrying independent constitutive CLEC16A mutations [14].…”
Section: Introductionsupporting
confidence: 89%
“…Therefore, cellular changes in clec16a crispants were assessed despite their normal brain size. Several studies have shown the involvement of CLEC16A in endosomal trafficking and autolysosomal clearance, with accumulation of autophagosomes in Purkinje neurons of adult Clec16a knockout mice (Hain et al 2021;Redmann et al 2016). In addition, defective retromer-dependent trafficking results in accumulated autolysosomes (Seaman 2021).…”
Section: Clec16a Depletion In Zebrafish Results In Accumulated Autoly...mentioning
confidence: 99%
“…Clec16a knockout (KO) mice present with severe neurodegeneration, loss of cerebellar Purkinje cells associated with accumulated autophagosomes and activation of autophagy marker LC3 (Redmann et al 2016). Moreover, the impaired secretory capacity of Clec16a deficient neuronal cells induces ER stress in a conditional KO Clec16a mouse model (Hain et al 2021). The physiological ER stress response is essential during normal brain development by acting as a protective and intrinsic regulator of protein synthesis and metabolic homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that activation of ISGs is a shared feature of neuronal injuries and that ISG15 may be a suitable biomarker for detecting neuronal injuries in the central nervous system (CNS) [196]. Consistent with these findings, upregulation of ISG15 was observed in neuronal tissues and has been linked to degeneration of sensory neurons in Clec16a knockout mice [197]. Together, these results suggest that elevated ISG15 is associated with neurodegeneration.…”
Section: Isg15 In Neurodegenerative Disordersmentioning
confidence: 63%